Prohibiting Pueblo - Tekavec, Tara L., author; Morales, Juan, advisor; Huddock, Sandy, committee member; Taylor, Ted, committee member (Colorado State University. Libraries, 2012)
This is a creative writing thesis of forty-three poems that tell the story of Prohibition. It focuses largely on what was happening during this time in Pueblo, Colorado, but it also offers a national perspective. This collection started with and is centered around family stories from the Prohibition era. After much research, it evolved to include the Mafia, originally known as the Black Hand, and the fights that resulted. Emphasis is also put on women during this time period and how they were changing and evolving. Above all, it urges a New Historicist reading of the poems and provides historical information to allow background for this.